Implications from the application of stable isotopes in freshwater food webs east of the Hu Line, China - Shiling Xu; Jiaxin Wang; Yan Zuo; Longfei Ma; Jun Chen; Zichao Zhang; Ping Xie; Jia Yu; Jie Liu (Ecological Indicators)
Trophic relationships between species in ecosystems are characterized by food webs. However, there is less research on the differences in food web characteristics at larger spatial scales. This study discusses the spatial variations in food web structures across 13 freshwater ecosystems located east of the Hu Line, based on stable isotope techniques. The results show that there are significant spatial differences in the structure of the food web of the studied ecosystem, which is associated with human activities, seasonal variation, environmental factors, etc. Additionally, this study describes how fish exhibit different dietary strategies in response to the fluctuations of food resources, such as the temporal lag of stable isotopic values and changes in trophic ecological niche width (overlap or differentiation). Finally, we summarize the potential uncertainties in the application of stable isotope techniques, emphasizing the necessity to carefully consider these uncertainties when utilizing stable isotope data for ecological research to ensure the accuracy and reliability of the results. The study provides theoretical support for the regional-scale management of freshwater ecosystems.